Micronutrient status and intake in the UK – where might we be in 10 years' time?. Issue 1 (7th February 2016) - Miller, R.; Spiro, A.; Stanner, S.
Abstract: Poor dietary choices not only manifest in obesity, which is currently the main public health focus in the UK, but can also lead to inadequate micronutrient intakes, with implications for health. Recent dietary survey data and measurements of status biomarkers have highlighted folate, vitamin D, calcium, iron and iodine to be amongst the micronutrients of most concern for particular subgroups of the UK population. Those most vulnerable to inadequate intakes of these micronutrients include adolescents, ethnic minorities and lower socio‐economic groups. Teenage girls and women of childbearing age are of particular concern because of their high requirements for some micronutrients and the impact poor micronutrient intakes can have on the health of their offspring. Yet, compared to other food concerns, relatively little importance seems to be given by consumers to the micronutrient density of foods. This review explores different factors that may influence micronutrient intakes and status over the following decade and beyond. Over the next few years, it is likely that the micronutrients of concern remain similar, although continuation of dietary trends could result in further decreases in iron and calcium intakes. In an obesogenic and sedentary environment, where many people are being encouraged to reduce their energy intakes, increasing the micronutrient density of the diet is essential to prevent a concurrent decrease in micronutrient intake. Investment in fortification policies/practices or sustained government programmes aimed at raising awareness of micronutrients of most concern or encouraging supplementation, for example focusing on folate and vitamin D, could considerably improve population micronutrient intakes. Over the longer term, with sufficient investment in research and support from healthcare professionals and the food industry, adequate micronutrient intakes could be achieved across the UK population. However, global food security issues, including retaining food supply in response to an increase in demand for food, energy and water, and changing climate, could potentially hamper these efforts.